2014
DOI: 10.1371/journal.pone.0103502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vascular Formed Endothelial Cell Network on the Invasive Capacity of Melanoma Using the In Vitro 3D Co-Culture Patterning Model

Abstract: In vitro three dimensional (3D) cancer models were developed to observe the invasive capacity of melanoma cell spheroids co-cultured with the vascular-formed endothelial cell network. An array-like multicellular pattern of mouse melanoma cell line B16F1 was developed by magnetic cell labeling using a pin-holder device for allocation of magnetic force. When the B16F1 patterned together with a vascular network of human umbilical vein epithelial cells (HUVEC), spreading and progression were observed along the HUV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…We also confirmed that the viability of human cancer cells labeled with MCLs is not decreased by the capture and filtering process (98.8% ± 1.1% before and 97.6% ± 0.9% after) . Furthermore, several research groups, including our group, showed that MCLs do not affect the viability, proliferation, or differentiation of other cell types within the range of magnetite concentration tested . According to these observations, the viability and proliferation of CTCs in clinical samples should not be inhibited by MCLs under the conditions used in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We also confirmed that the viability of human cancer cells labeled with MCLs is not decreased by the capture and filtering process (98.8% ± 1.1% before and 97.6% ± 0.9% after) . Furthermore, several research groups, including our group, showed that MCLs do not affect the viability, proliferation, or differentiation of other cell types within the range of magnetite concentration tested . According to these observations, the viability and proliferation of CTCs in clinical samples should not be inhibited by MCLs under the conditions used in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…A pin‐holder device was used to position the captured CTCs on the culture dish with or without a fibroblast feeder layer, as described previously . A culture dish with or without the feeder layer was placed on the pin‐holder device with a magnet; to this dish, we added the whole recovered DMEM containing CTCs in order to seed the magnetically labeled CTCs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have developed a cell patterning method for mammalian cells using magnetite nanoparticles and the pin-holder magnetic device for single cell analysis (Ino et al, 2008;Okochi et al, 2013a;Okochi et al, 2013b;Okochi et al, 2009;Yamamoto et al, 2014). In this method, we used magnetite cationic liposomes (MCLs), which are cationic liposomes containing 10 nm-magnetite nanoparticles.…”
Section: Introductionmentioning
confidence: 99%